Quality of Life in End Stage Renal Disease and Its Related Factors - F Rafii; Masoumeh Rambod; Agha Fatemeh Hosseini (Iran University of Medical Sciences, 2010)
Background and Aim: End stage renal disease affects the daily lives of many patients and families due to the changes in their health status, life style and roles. These changes impact the quality of their lives. Regarding the increasing number of these patients in Iran, this study was conducted to examine the quality of life and its related factors in patients with end stage renal disease.   Material and Method : This was a descriptive- correlational study. Two hundred and two hemodialysis patients admitted to the hospitals affiliated to Iran University of Medical Sciences were recruited using convenience sampling. Data was collected using Ferrans and Power Quality of Life Index (QLI) dialysis version and analyzed using SPSS-PC version 14.   Results : Most patients had a good quality of life. There were statistically significant relationships between financial status, marital status and number of children, and the quality of life (P≤ %5).   Conclusion : Regarding the factors related to the quality of life in these patients, renal nurses are needed to pay more attention to the patient characteristics and demographics. Further longitudinal research is suggested.